Taux de roulement et permanence de l’emploi dans l’industrie canadienne - Jenness, R. (L'Actualité économique)

(untitled) (HEC Montréal, 1974)
AbstractThis study poses the question: "How long will the average new employee likely stay with his employer? This question has considerable relevance to the study of labour market activity, and to the obverse question: "How likely will a person, once employed, be unemployed again?" This paper explores the relevance of the tenure question on a number of fronts, and then develops a simple model for estimating the expected tenure of workers joining specific industries in Canada. Although the findings are based on somewhat dated statistics and lack a vector related to age, sex and other personal characteristics, they nonetheless confirm within reasonable degrees of confidence that the average new employee will remain with his employer a remarkably short time—less than two years in most industries and only a few months in some others. They suggest that employers are wise to defer costly training, pension and other non-wage expenditures until their new employees have built up some attachment to the firm. By the same token they affirm the usefulness of public income support programs to tide those who are laid off or quit through the transition to their next job, and for public retraining and mobility facilities to make the investments in human skills and allocation that employers will not.